2022
DOI: 10.1002/mma.8429
|View full text |Cite
|
Sign up to set email alerts
|

Electro‐magneto‐hydrodynamic Eyring‐Powell fluid flow through micro‐parallel plates with heat transfer and non‐Darcian effects

Abstract: The Eyring-Powell fluid flow between two micro-parallel plates in the context of electro-magneto-hydrodynamic is the focus of the article. The Lorentz force, which is generated by the interactions of a vertical magnetic field and an externally imposed horizontal electrical field, is presumed to be unilateral and onedimensional. Using the Darcy-Brinkman-Forchheimer model, the medium of the micro-parallel plates is assumed to be porous. The energy equation evaluates the effect of viscous dissipation and joule he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…In their research, Sharma et al [20] investigated the combined effect of thermophoresis and Brownian motion on magnetohydrodynamic mixed convective flow over an inclined stretching surface, considering the influence of thermal radiation and chemical reaction. Bhatti et al [21] investigated the electromagneto-hydrodynamic Eyring-Powell fluid flow through microparallel plates, considering heat transfer and non-Darcy effects. Khan et al [22] conducted an investigation on the flow of micropolar base nanofluid over a stretching sheet in the presence of thermal radiation and a magnetic dipole.…”
Section: Eejp 4 (2023)mentioning
confidence: 99%
“…In their research, Sharma et al [20] investigated the combined effect of thermophoresis and Brownian motion on magnetohydrodynamic mixed convective flow over an inclined stretching surface, considering the influence of thermal radiation and chemical reaction. Bhatti et al [21] investigated the electromagneto-hydrodynamic Eyring-Powell fluid flow through microparallel plates, considering heat transfer and non-Darcy effects. Khan et al [22] conducted an investigation on the flow of micropolar base nanofluid over a stretching sheet in the presence of thermal radiation and a magnetic dipole.…”
Section: Eejp 4 (2023)mentioning
confidence: 99%
“…Magnetohydrodynamic has many usage in advanced manufacturing and other industries, which include films and drawing plastic wires, extruding polymers in the melting spinning processes, glass fiber production and crystal growth, manufacturing of foods and electronic chips, thermal energy storage, flow through filtering devices, fluid film in condensation processes, electrochemical processes and others. Several scholars have applied physical parameters to explore magnetohydrodynamic boundary layer flow across stretching and shrinking surfaces [3,7,8,21,26]. Additionally, since it has numerous uses in the medical and industrial sciences, nanotechnology has earned a great deal of interest from researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Bhatti et al 23 studied natural convection non‐Newtonian electro‐MHD dissipative flow through a microchannel containing a non‐Darcy porous medium using the homotopy perturbation method. Bhatti et al 24 studied electro‐magneto‐hydrodynamic Eyring–Powell fluid flow through microparallel plates with heat transfer and non‐Darian effects. Bhatti et al 25 found the numerical solutions of hybrid nanofluid flow over a circular elastic surface with a non‐Darcy medium.…”
Section: Introductionmentioning
confidence: 99%